The developement of an analysis system to assist in the correction of inefficiencies in starts and turns for elite competitive swimming - Mason, B.; Mackintosh, C.; Pease, D. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this paper is to provide the reader with information concerning the purpose, the structure, the capabilities and the analyses provided by the Wetplate computer programme and its associated data capture equipment. Since its development and its success in helping coaches eliminate technique inefficiencies in elite swimmers` starts and turns, coaches have been bringing their swimmers from all over Australia in increasing numbers to take advantage of Wetplate`s attributes. The presentation will provide examples of how the Wetplate analysis has been able to assist in the performance enhancement of elite Australian swimmers.